Effectiveness of Al-Quran Auditory Therapy and Music Therapy on Pain Quality in Coronary Heart Disease Patients at Ulin General Hospital - Milasari, .; Hamzah, .; Solikin, . (KnE Life Sciences, 2021)
Heart disease is the number one cause of death globally; an estimation shows that 17.7 million people die because of cardiovascular disease. 7.4 million deaths are caused by coronary heart disease. The main symptoms of coronary heart disease are chest pain (angina), feeling depressed, squeezed or choked with the location of the pain at the back of the left breastbone spreading from the bottom of the upper arm, left shoulder, to the neck or lower jaw. Pain management can be done with non-pharmacological techniques of Al-Quran auditory therapy and music therapy. The purpose of this study is to determine the effectiveness of Al-Quran auditory therapy and music therapy on the quality of pain in patients with coronary heart disease. This research is a quantitative research with Quasy Experimental research design using two pre and post design approach involving 28 respondents. Measurement of pain level by using Numerical Rating Scale. The results showed that both therapy had an effect on the quality of pain of coronary heart disease patients. The mean decreasing of pain in the group of auditory therapy Al-Quran is bigger than the music therapy group the results of the mean 1.286. So it can be deduced that Al-Quran auditory therapy is more effective in reducing pain in patients with coronary heart disease. The suggestion of this study may provide additional information for response-related pain relief. Keywords: CHD, Pain, Al-Quran, Music